Key indicators for maintenance performance measurement: The aircraft galley and associated equipment manufacturer case study - Rungchat Chompu-Inwai (2018)
The aim of this research was to develop a maintenance performance measurement model, based on three main steps, these being: (1) identify and screen factors affecting maintenance performance, (2) identify relevant key indicators for the measurement of maintenance performance, and (3) apply those key indicators developed as part of a manufacturing company case study. Using three reference models - the Cost of Poor Maintenance Model, the Malcolm Baldrige National Quality Award and the Context-Input-Process-Product assessment model, the first step was to identify a number of factors relevant to maintenance performance, as taken from previous research. The resulting 105 factors were a mixture of quantitative and qualitative factors, and were categorized according to the four perspectives within the Balances Scorecard, these being learning and growth, internal process, customer, and finance. A questionnaire used to screen those factors affecting maintenance performance was then distributed to stakeholders and maintenance staff at the case study manufacturer, which produces aircraft galleys and associated equipment. An analysis was conducted using descriptive statistics, and according to the study results, 20 factors were found to most affect maintenance performance. Once the factors had been identified, a second step was carried out - to identify the key maintenance performance measurement indicators, of which 6 were financial, 6 were customer related, 5 were related to the internal process and 3 indicators were linked to learning and growth. The final step was to employ the indicators obtained as part of a study of the case study manufacturer, in order to evaluate maintenance performance there. The results of the evaluation, once obtained, helped develop a framework that could be used to improve the maintenance system. © 2013 IEEE.